Covid-19; Hoax and Efforts to Prevent it from the Perspective of Islamic Law - Teguh Mulyo, A Mufrod (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
The development of an era or what is commonly known as globalization indicates progress in all fields, such as technology, transportation, information, and communication. These advances certainly impact all aspects of life in the world, making it easier to actualize. The consequence of this convenience is the frequent dissemination of hoax information on social media. Thus, this paper will discuss the review of Islamic law related to hoaxes and their prevention efforts in the Covid-19 case study. This study uses a descriptive-analytical approach, which describes a review of Islamic law related to hoaxes and how to prevent them in the millennial era. The results of this study, we must refer to the Qur'an because it is a preventive measure to deal with the reporting of hoax news, Allah condemns someone who brings false news, and in the Qur'an, it is explained so that Muslims always tell the truth and based on facts, every Muslim must be patient and critically examine the information that emerges.